Generational factor in socialization of personality and the formation of spiritual unity of society - Rybalka, V. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article presents data on the study of the generation factor role in the socialization of personality and in the formation of the spiritual unity of the society, the definition of this factor, the characteristic of the generation concept, generations classification considered the mission of each of them, the types of generations differentiation, psychological factors of the generation of personality movement, depending on its orientation , intelligence, temperament, examples of the organization of harmonious coexistence and cooperation of generations in addressing global and historical projects. The current issues for further study and the usage of the generation factor are formulated to improve the socialization of the individual and for strengthening the spiritual unity of the different generations in society.